Correlation between H. pylori infection and COVID-19 among a sample of dental students - Christine Mikhail; Samia El-Shishtawy; Marwa El Nawawy; Layla Hafed; Seham Hazem El-Ayouti; Nada Noureldin; Sally Ibrahim; Sahar El Refai; Rania Hassan Shalaby (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
COVID-19 infection, the most prevalent deadly pandemic in the world, has been correlated to the highly prevalent Helicobacter Pylori (H.P.) infection which is considered a major cause for gastric carcinoma and it seems to be an important risk factor that predisposes and augments the course of COVID-19 infection, via increasing the expression of angiotensin-converting enzyme-2 receptors in the gastrointestinal tract, to which COVID- 19 binds to enter the cell, causing gastrointestinal symptoms during the course of the disease. The aim of this study was to investigate any possible correlation between  H. pylori infection and COVID-19 among a sample of dental students, at the faculty of Dentistry, Fayoum University, Egypt. Methods & Subjects: This study was carried out from October to November, 2022 among a sample of 100 dental students. Those who reported the characteristic symptoms of COVID-19 infection and whose infection was confirmed by nasopharyngeal (NS) PCR-RT swabs, were included in the study. All students were screened for anti- H.P. using saliva samples, analyzed with an enzyme-linked immunosorbent assay (ELISA). All were evaluated for manifestations of COVID-19 infection, severity of the course, hospitalized days because of the virus and outcome of the disease process.